FACTORS INFLUENCING CONSUMERS' INTENTION TO PURCHASE ORGANIC FOOD IN KHULNA CITY, BANGLADESH - Puspendu Debnath,; Sabrina Akter,; Md. Toriqul Islam, (The Indonesian Journal of Social Studies, 2025)
Organic food is widely regarded as clean, healthy, and sustainable consumption and its demand is increasing globally daily because of the adverse health effects of inorganic food. Quantitative analysis of the factors of individual’s decisions to purchase organic food is lacking in the existing literature. By surveying 210 households from one southwestern district of Bangladesh, this study examines the influencing factors of purchasing organic food and explores policy implications. To find the impact of health consciousness, environmental consciousness, social influences, and attitudes on organic food purchase intention, this study employs confirmatory factor analysis and structural equation modeling. The findings of structural equation modeling reveal that health consciousness, environmental consciousness, and social influences have a significant relationship with purchase intention. However, the mediating factor called attitude has no impact on the purchase decision of organic food. The findings of this study have substantial implications for marketers and policymakers.